2014
DOI: 10.1097/fpc.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Association of FCGR2A with the response to infliximab treatment of patients with rheumatoid arthritis

Abstract: We found an association of the FCGR2A 131R allele with poor response to INX. This finding could be of utility to understand the mechanisms behind treatment failure and contribute to biomarker panels for INX response prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…10 In addition, these loci seem to show time-specificity in their association with response to TNFi, and most GWAS have combined multiple follow-up times. The time-specificity is supported by the PTPRC and IL10 SNPs, which were only associated at the same follow-up time as in previous studies 15,8,9 and by other two biomarkers of response to TNFi that have previously shown time-specificity 25 (Montes A. et al Arthritis Research and Therapy, in press). These caveats apply also to a study that did not replicate association of rs1091956 in 233 patients assessed at various times of follow-up.…”
Section: Discussionmentioning
confidence: 64%
“…10 In addition, these loci seem to show time-specificity in their association with response to TNFi, and most GWAS have combined multiple follow-up times. The time-specificity is supported by the PTPRC and IL10 SNPs, which were only associated at the same follow-up time as in previous studies 15,8,9 and by other two biomarkers of response to TNFi that have previously shown time-specificity 25 (Montes A. et al Arthritis Research and Therapy, in press). These caveats apply also to a study that did not replicate association of rs1091956 in 233 patients assessed at various times of follow-up.…”
Section: Discussionmentioning
confidence: 64%
“…Candidate-gene studies, although limited to the knowledge of the biological pathways associated to a particular disease or trait, have also been successful in identifying new candidate loci for the response to anti-TNF therapy [ 9 ]. One such candidate gene is FCGR2A , encoding an Fc receptor mainly expressed in macrophages and dendritic cells [ 10 ], and for which there is increasing evidence supporting its association to anti-TNF therapy in RA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, rs1801274 is a strong candidate for influencing the response to IgG-based treatments, like anti-TNF agents. There is increasing evidence that variation at this SNP is associated with a differential response to anti-TNF therapy in RA [ 11 , 25 ]. Importantly, there is recent evidence that the association between FCGR2A and the clinical response in RA could be dependent on the type of anti-TNF agent, with a significant association in patients treated with infliximab [ 25 , 26 ] and a lack of association on etanercept-treated patients [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Significant association was found between the FCGR2A H131R polymorphism and the response to treatment with infliximab, but not with the other two TNF inhibitors, etanercept and adalimumab. 38 In addition, IL-6R polymorphisms rs12083537, rs2228145 and rs4329505 have been shown to be potential predictors for response to tocilizumab in RA. 39 By a three-stage trans-ethnic meta-analysis, Okada et al 40 not only discovered 42 novel RA risk loci at a genome-wide level of significance, but also demonstrated that these genes are the targets of approved therapies for RA, including tocilizumab (anti-IL6R), tofacitinib (Janus-activated kinase 3 inhibitor), and abatacept (cytotoxic T-lymphocyte-associated protein 4 immunoglobulin).…”
Section: Clinical Application Of Genetic Studies In Ramentioning
confidence: 99%